Chemical profiling and total quality assessment of Isodon japonica using data-independent acquisition mode combined with superimposed multiple product ion UHPLC-Q-TOF-MS and chemometric analysis. Issue 3 (11th January 2019) - Jin, Yiran; Tian, Tingting; Ma, Yinghua; Hou, Ludan; Guan, Shuai; Sun, Wenjing; Du, Yingfeng; Zhang, Lantong
Abstract : In this paper, a combined analytical strategy was developed and aimed at rapid characterization and quantitation of ent -kaurane diterpenoids in Isodon japonica using UPLC-Q-TOF-MS/MS. Abstract : In this paper, an analytical strategy combined data acquisition with a practical mining strategy aimed at rapid characterization and quantitation of ent -kaurane diterpenoids in Isodon japonica using ultra high-performance liquid chromatography-triple time-of-flight mass spectrometry (UPLC-Q-TOF-MS/MS). First, an effective self-built filter template based on drug phase I/II metabolic reaction theory and a components library data set were established. Second, the mass spectra of ent -kaurane diterpenoid standards were studied and their mass spectrum cleavage pathways were summarized. Next, the methanol extract of this herb was studied by data-independent acquisition mode (DIA). With the aid of a self-built filter template, the peaks of ent -kaurane diterpenoids were easily picked out and rapidly classified as ent -kaurane diterpenoids from a complex matrix. A total of 24 ent -kaurane diterpenoids were structurally identified. Meanwhile, the self-built filter template provided a convenient and fast method for the structural characterization and Isodon japonica was used to illustrate this approach for the first time. Furthermore, eight major bioactive diterpenoids were simultaneously quantified by a newly developed superimposed multiple product ion (SMPI) with UPLC-Q-TOF-MS/MS method. Principal component analysis (PCA) revealed significant differences in different batches of samples. These combined qualitative and quantitative methods were used to provide a potential approach for the holistic quality evaluation of traditional Chinese medicine (TCM) and its preparations.